2016
DOI: 10.1002/jor.23284
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of water content distributions in degenerated human intervertebral discs

Abstract: The objective of this study was to investigate the spatial and temporal variations of water content in intervertebral discs during degeneration and repair processes. We hypothesized that the patterns of water content distribution in the discs are related to the intensity patterns observed in T2-weighted MRI images. Water content distributions in the mildly (e.g., 80% viable cells in the disc, 2.3% decrease in disc height) and moderately (e.g., 40% viable cells in the disc, 9.3% decrease in disc height) degener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…Specifically, changes in CEP permeability to nutrients has been operationalized in several ways. In some cases, the boundary concentration of nutrients (both glucose and oxygen) at the CEP was reduced down to 50% ( Kauppila, 1995 ; Selard et al, 2003 ; Malandrino et al, 2014 ), 30% ( Zhu et al, 2012 ; Gu et al, 2014 ), or even 0% ( Zhu et al, 2014 , 2016 , 2017 ) of the normal physiological values. Some other studies simulated the effect of CEP calcification by reducing the CEP exchange area with the nucleus pulposus (NP) and AF (Selard and Urban, 2003), or by reducing its water content ( Soukane et al, 2007 ; Shirazi-Adl et al, 2010 ; Jackson et al, 2011a ), thus reducing solute diffusivity into the core of the IVD tissue.…”
Section: Nutritional Supplymentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, changes in CEP permeability to nutrients has been operationalized in several ways. In some cases, the boundary concentration of nutrients (both glucose and oxygen) at the CEP was reduced down to 50% ( Kauppila, 1995 ; Selard et al, 2003 ; Malandrino et al, 2014 ), 30% ( Zhu et al, 2012 ; Gu et al, 2014 ), or even 0% ( Zhu et al, 2014 , 2016 , 2017 ) of the normal physiological values. Some other studies simulated the effect of CEP calcification by reducing the CEP exchange area with the nucleus pulposus (NP) and AF (Selard and Urban, 2003), or by reducing its water content ( Soukane et al, 2007 ; Shirazi-Adl et al, 2010 ; Jackson et al, 2011a ), thus reducing solute diffusivity into the core of the IVD tissue.…”
Section: Nutritional Supplymentioning
confidence: 99%
“…For instance, Noailly et al (2007) compared theoretical predictions for spinal range of motion with cadaveric measurements to validate their computational model. Similarly, Zhu et al (2017) also used experimental results for disc water content to validate their computational prediction of disc degeneration. Recently, bioreactor studies have been used to validate finite elements models ( Gatenbein et al, 2015 ).…”
Section: Limitations Of the Models And Future Directionsmentioning
confidence: 99%
“…A previous study reported water content to decrease with the degenerative process of the intervertebral disc. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al developed a cell‐activity‐coupled mechano‐electrochemical finite element model of the IVD with simulated degenerative changes and biological treatments. IVD spatial water content patterns were found to be very sensitive to degenerative state and to biological treatments that increased cell density, increased glycosaminoglycan synthesis rate, and decreased glycosaminoglycan degradation rate …”
Section: Biomechanical Factors In Ivd Degeneration and Repairmentioning
confidence: 99%
“…IVD spatial water content patterns were found to be very sensitive to degenerative state and to biological treatments that increased cell density, increased glycosaminoglycan synthesis rate, and decreased glycosaminoglycan degradation rate. 19…”
Section: Biomechanical Factors In Ivd Degeneration and Repairmentioning
confidence: 99%